Evaluation of the rehabilitation process after ACL rupture in childhood and adolescence - Böker, E.; Janke, C.; Brunn, S.; Brock, D.; Jurig, K.; Witt, M. (Deutsche Zeitschrift für Sportmedizin, 2022)
Summary